AuPt Bimetallic Nanozymes for Enhanced Glucose Catalytic Oxidase - Chen, Feixiang; Song, Tianlin (Frontiers in Chemistry, 2022)
Au metal nanoparticles as artificial nanozymes have attracted wide interest in biotechnology due to high stability and easy synthesis. Unfortunately, its catalytic activity is limited by the uniform surface electron distribution, fundamentally affecting the oxidation efficiency of glucose. Here, we synthesized AuPt bimetallic nanoparticles with unique surface electron structure due to the coupling effect of the two metal components, achieving improved glucose catalytic oxidase. Because of the effective work function difference between the two metals in AuPt, the electrons will transfer from Au to accumulate on Pt, simultaneously contributing to the substantial enhancement of Au-induced glucose oxidase and Pt-induced catalase performance. We systematically studied the enzyme-catalytic efficiency of AuPt with varied two metal proportions, in which Au:Pt at 3:1 showed the highest catalytic efficiency of glucose oxidase in solution. The AuPt nanoparticles were further co-cultured with cells and also showed excellent biological activity for glucose oxidase. This work demonstrates that the physicochemical properties between different metals can be exploited for engineering high-performance metal nanoparticle-based nanozymes, which opens up a new way to rationally design and optimize artificial nanozymes to mimic natural enzymes.